Code Mixing in Reizuka Ari’s TikTok Vlogs: An Analysis of Indonesian–English Language Use - Nita Fauziah (Pustaka Digital Indonesia, 2026)
This research is urgent because analyzing code mixing in Reizuka Ari’s TikTok vlogs reveals how Indonesian–English language use on social media shapes contemporary communication practices and youth linguistic identity. This research is motivated by the phenomenon of Digital Multilingualism in the digital era which has transformed social media into a space for identity negotiation through the use of language..The purpose of this study is to identify and classify Indonesian-English code mixing patterns in Reizuka Ari's TikTok vlog..Using a descriptive qualitative method with Muysken's theoretical framework, this study analyzed 15 speech data from the video